2018
DOI: 10.11607/jomi.6417
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Dental Implants Following Sinus Floor Augmentation: A Systematic Review and Meta-Analysis of Clinical Trials with at Least 3 Years of Follow-up

Abstract: Current evidence suggests that implants in augmented sinuses have high survival rates, with smoking playing a potentially important negative role in their prognosis. Both indirect and direct maxillary sinus floor augmentation seem to have a low frequency of manageable complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 0 publications
7
41
0
1
Order By: Relevance
“…Maxillary sinus floor augmentation (MSFA) was originally developed by Tatum in the mid-seventies and afterwards described by Boyne and James in 1980 [1,2]. Nowadays, MSFA applying the lateral window technique is the most commonly used surgical procedure to increase the vertical alveolar bone height of the posterior maxilla before or in conjunction with placement of dental implants, and the treatment outcome involving various types of grafting materials have been documented in systematic reviews and meta-analyses [3][4][5][6][7][8][9][10]. Autogenous bone graft is generally considered the preferred grafting material for MSFA due to its osteoinductive, osteogenic and osteoconductive characteristics [11].…”
Section: Introductionmentioning
confidence: 99%
“…Maxillary sinus floor augmentation (MSFA) was originally developed by Tatum in the mid-seventies and afterwards described by Boyne and James in 1980 [1,2]. Nowadays, MSFA applying the lateral window technique is the most commonly used surgical procedure to increase the vertical alveolar bone height of the posterior maxilla before or in conjunction with placement of dental implants, and the treatment outcome involving various types of grafting materials have been documented in systematic reviews and meta-analyses [3][4][5][6][7][8][9][10]. Autogenous bone graft is generally considered the preferred grafting material for MSFA due to its osteoinductive, osteogenic and osteoconductive characteristics [11].…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate implant placement in the areas of the posterior maxilla with insufficient alveolar height, a maxillary sinus augmentation (MSA) technique using a lateral approach was invented (Boyne & James, 1980). Over the last 40 years, a variety of modifications to this technique has been published and clinical trials have confirmed its predictability and long‐term efficacy (Antonoglou et al., 2018; Chanavaz et al., 1995; Pjetursson et al., 2008; Raghoebar et al., 2019; Tatum et al., 1993). The first and one of the best grafting materials for this intervention is the autologous bone (AB), which was considered by many authors as the "gold standard.” It possesses osteoinductive, osteoconductive, and osteogenic capabilities, but also involves donor‐site morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Graziani et al reported a wider range of implant survival in MSFA (36% to 100%) than in implants placed in the pristine posterior maxilla (73% to 100%) at patient level in their systematic review [ 17 ]; however, they could not elucidate the reasons for the variability due to the heterogeneity of studies. The effects of multiple variables, including the sinus elevation technique, use and type of graft material, use of a barrier membrane over the lateral window, and timing of implant placement, were studied or mentioned in some systematic reviews about the clinical performance of implants with MSFA [ 9 , 17 , 18 ]. These factors can hinder a consistent result of studies on those implants.…”
Section: Introductionmentioning
confidence: 99%